Adsorption of 2, 3, 7, 8-tetrachlorodibenzao-p-dioxin (TCDD) on graphane decorated with Ni and Cu: A DFT study. (March 2018) - Zhou, Qingxiao; Su, Xiangying; Yong, Yongliang; Ju, Weiwei; Fu, Zhibing; Li, Xiaohong
Abstract: Dioxins are highly toxic to humans and the environment, and developing effective materials to detect the organic pollutants has attracted much attention. Hydrogenated graphene (graphane) with wide band-gap and low dimension might be one of the promising sensors to detect 2, 3, 7, 8-tetrachlorodibenzao-p-dioxin (TCDD) molecules. Using density functional theory (DFT) method, the adsorption of TCDD molecules on pure, H-defected, and transition-metal (Ni and Cu) decorated graphane was investigated. The results indicated that the adsorption stability of TCDD molecules on graphane was improved by the H-vacancy. Furthermore, the H-vacancy produced a half-metallic behavior, which was due to the defect released the p electron of C atoms. After introducing the dopants (Ni and Cu), the adsorption energies and charge transfer of TCDD molecules were enlarged, which suggested that the Ni and Cu increased the sensitivity of graphane to the TCDD molecules. Furthermore, the change of the band gaps in the graphane substrates by the adsorption of TCDD molecules can change the conductance of the substrates, which can be seen as electric signal to detect TCDD molecules. Highlights: The appearance of H-vacancy improved the chemical reactivity of graphane. The introducing of dopants enhanced the adsorption stability of TCDD molecules. The adsorption of TCDD molecules induced obvious change of band gaps to the graphane substrates.